STRUCTURE OF TECHNICAL EDUCATION AND VOCATIONAL TRAINING IN PAKISTAN - Shah, Iftikhar Hussain (Journal of Technical Education and Training, 2010)
The main purpose of the study was to investigate the present profile of technical education, their problems and prospects and to find out the causes in case of slow implantation and low achievements of target. The sample of the study consisted of 40 experts of technical education, 35 principals, 175 teachers and 350 students which were selected randomly. A questionnaire was developed for principals, teachers and students of polytechnic institutes/colleges of technology. This questionnaire consisted of 59 items. An interview was also conducted with the experts of technical education about problems and suggestion regarding. The data was statically analyzed using percentages and chisquare test. The study revealed that objectives and policies were not matching. It was further found that major causes of the problems were political instability and improper monitoring, out dated curricula, inadequate budget, outdated teaching methodologies, lack of proper linkage between technical education and industry. The study recommended that a National Council for Technical Education may be activated to regulate technical education. It is recommended to strengthen the public-private partnerships. The study also recommended that national occupational skills standards, curricula and trade testing certification system may be developed.